2019
DOI: 10.1002/sctm.19-0113
|View full text |Cite
|
Sign up to set email alerts
|

Rat Mesenchymal Stromal Cell Sheets Suppress Renal Fibrosis via Microvascular Protection

Abstract: Renal fibrosis is one of the largest global health care problems, and microvascular (MV) injury is important in the development of progressive fibrosis. Although conventional cell therapy suppresses kidney injury via the role of vasoprotective cytokines, the effects are limited due to low retention of administered cells. We recently described that transplantation of hepatocyte growth factor (HGF)transgenic mesothelial cell sheets showed a remarkable cell survival and strong therapeutic effects in a rat renal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…In this research, we sought to detect the antifibrotic effect of combination treatment. It has been confirmed that transplantation of HGF-transgenic mesothelial cell sheets show therapeutic effects on renal fibrosis 26 and can be used as an antifibrotic agent. 27 The present study verified that HGF suppressed the progression of renal fibrosis at different concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…In this research, we sought to detect the antifibrotic effect of combination treatment. It has been confirmed that transplantation of HGF-transgenic mesothelial cell sheets show therapeutic effects on renal fibrosis 26 and can be used as an antifibrotic agent. 27 The present study verified that HGF suppressed the progression of renal fibrosis at different concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, a wounded skin mouse model treated with mesenchymal stem cell sheets formed organized blood vessels and exhibited increased expression of angiogenic factors, thus leading to tissue healing at twenty-one days post-surgery [ 63 ]. Likewise, mesenchymal stem cell sheets were shown to improve kidney function by reducing fibrosis and microvasculature damage in a renal ischemia-reperfusion injury rat model fourteen days post-surgery [ 64 ]. Furthermore, mesenchymal stem cell sheets have been shown to restore function, while decreasing fibrosis in a chronic liver injury mouse model nine days after surgery [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in real practices, the collection of endometrial cells is not a recommended option because it is hard to collect adequate quantity of endometrial cells from the uterus and collection may also be interfered by certain inflammatory or contagious diseases, apart from the harm out of invasive procedures (Logan et al, 2018). Stem cell sheet engineering (SCSE) gradually becomes an important research direction due to the minimal invasiveness, autologous tissue supply, multi-differentiation potential, high proliferation, growth factor secretion and signaling transduction of stem cells (Shum et al, 2017;Hsu et al, 2019;Imafuku et al, 2019).…”
Section: Stem Cell Sheet Engineering In the Endometrium Regenerationmentioning
confidence: 99%